Polyester fiber paper pulp as well as preparation method and application thereof

By using beating and coated modified titanium dioxide technology during papermaking, the problem of insufficient dispersion and wettability of chemical fibers is solved, and the high mechanical properties and environmentally friendly recycling of paper are achieved.

CN119686146AActive Publication Date: 2025-03-25DONGHUA UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510194329.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

Chemical fibers have problems with insufficient dispersion and wetting during papermaking, which makes it difficult to disperse and easily flocculate, and their waste paper recycling is limited.

Method used

Polyester fiber pulp is prepared by mixing staple fibers, water and inorganic salts and then beating them, and coated modified titanium dioxide is added to the spinning melt, and the dispersion and bonding fastness of the fibers are improved by drafting and alkali etching treatment.

Benefits of technology

The stable dispersion of fibers and good wettability of paper are achieved, the mechanical strength and tensile properties of paper are improved, and the dispersant is eliminated, which reduces environmental pollution and wastewater, and promotes the recycling of waste paper.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of papermaking, and relates to polyester fiber paper pulp as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing short fibers, water and inorganic salt, and pulping to obtain polyester fiber paper pulp; the preparation method of the short fiber comprises the following steps: spinning by adopting a spinning melt containing coating modified titanium dioxide, and then carrying out alkali etching treatment and cutting; the coated modified titanium dioxide comprises titanium dioxide and an oligomer coated on the surface of the titanium dioxide through a covalent bond; the preparation method of the coated modified titanium dioxide comprises the following steps: organically modifying titanium dioxide by using an amino-containing coupling agent to obtain coupling agent modified titanium dioxide, preparing an oligomer, mixing the oligomer with the coupling agent modified titanium dioxide, and reacting. The polyester fiber paper pulp can keep stable dispersion and can be applied to preparation of paper. The preparation method does not need to use a dispersing agent, so that the cost is saved, the environmental pollution and the wastewater amount are reduced, and later waste paper recycling is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of papermaking and relates to polyester fiber pulp and a preparation method and application thereof. Background Art

[0002] Papermaking is an important basic raw material industry closely related to the development of the national economy and social undertakings. At present, chemical fibers have been widely used in the papermaking industry to make special papers for various special purposes such as high temperature resistant, flame retardant, insulating, and wear-resistant. However, chemical fibers generally have a smooth surface, poor water wettability, and are easy to clump in water, resulting in the disadvantages of difficult dispersion, easy flocculation, and low bonding strength between paper fibers when chemical fibers are mixed with other fiber raw materials in the papermaking process. Simply adjusting the fiber type and fiber mixing ratio can only improve the fiber dispersibility and wettability to a limited extent, which limits the application of chemical fibers in papermaking.

[0003] In order to solve the problems of dispersibility and wettability of chemical fibers, some methods have been proposed in the prior art.

[0004] The most commonly used method is to add substances such as polyvinyl alcohol, sodium hexametaphosphate, methoxypolyethylene glycol, polyethylene glycol dimethyl ether, polyacrylamide, sodium polyacrylate, sodium silicate, gum, methyl amyl alcohol, etc. as dispersants to increase the wettability and diffusion coefficient of the paper. For example, patent CN220700751U discloses a quick-drying thermal sublimation transfer paper, patent application CN117604804A discloses a cellulose acetate fiber / plant fiber composite paper and its preparation method and application, and patent application CN115678316A discloses a method for preparing a titanium dioxide slurry for papermaking.

[0005] There is also a method of coating additives such as fatty acid salts on the surface of chemical fibers to improve the hydrophilicity and wettability of the fibers. For example, patent application CN107419573A discloses a method for preparing high-strength packaging chemical fiber paper.

[0006] There are also methods of increasing the wettability difference of paper by adjusting the fiber type and fiber mixing ratio while adding dispersants. For example, patent application CN114481354A discloses a polyphenylene sulfide ultrafine fiber and an ultra-short fiber and a preparation method thereof, and patent application CN118461354A discloses a synthetic fiber paper suitable for an ultra-low concentration inclined screen forming process and a preparation method thereof.

[0007] The common feature of the above existing methods is the use of a large amount of dispersants or additives. Although adding dispersants or additives to the slurry facilitates papermaking and improves the performance of the paper, it is easy to pollute the environment, and a large amount of wastewater will be generated during the production process, which increases the difficulty of sewage treatment. In addition, chemical fiber waste paper is not easy to degrade. With the demand for sustainable development, waste chemical fiber products must be recycled and reused. Since these dispersants or additives will be mixed with chemical fibers, the recycling and reuse of chemical fiber waste paper is greatly affected. Most of them can only be degraded by composting. This degradation treatment method is inefficient and causes waste of resources.

[0008] Therefore, there is an urgent need for a polyester fiber pulp and a preparation method thereof that can improve the dispersibility of the pulp and facilitate the recovery of waste paper. Summary of the invention

[0009] The purpose of the present invention is to solve the problems existing in the prior art and to provide a polyester fiber pulp and a preparation method and application thereof.

[0010] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0011] A method for preparing polyester fiber pulp, comprising mixing short fibers, water and inorganic salts and beating the mixture to obtain polyester fiber pulp;

[0012] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling (i.e., the filaments on different spinnerets are gathered together) → extrusion deformation (a pair of gear plates are used to deform the fibers, making them easy to entangle with each other and improving the mechanical properties of the paper) → preheating (because the filaments are thicker after bundling, it is difficult to fully contact with the hot roller during the drafting process, and thus the drafting effect cannot be guaranteed, so preheating is required) → drafting → heat setting → alkali etching → cutting;

[0013] The spinning melt contains 15-20wt% of coated modified titanium dioxide; the D50 particle size (i.e., median diameter or median particle size) of the coated modified titanium dioxide is 50-900nm; the coated modified titanium dioxide includes titanium dioxide and oligomers coated on the surface thereof by covalent bonds, and the oligomers differ from the matrix of the spinning melt only in average degree of polymerization, and the average degree of polymerization of the oligomers is 40-60;

[0014] The preparation method of the coated modified titanium dioxide is as follows: firstly, an amino-containing coupling agent (such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, etc.) is used to organically modify titanium dioxide to obtain coupling agent-modified titanium dioxide, and at the same time, an oligomer is prepared, and then the oligomer and the coupling agent-modified titanium dioxide are mixed and reacted;

[0015] The preparation process of the spinning melt is as follows: firstly, polyester and coated modified titanium dioxide are melt-blended to obtain a master batch, then the master batch is solid-phase thickened, and then the master batch after solid-phase thickening is melt-blended with polyester to obtain a spinning melt. During the solid-phase thickening process, the oligomer coated on the surface of titanium dioxide reacts with the polyester, thereby improving the bonding strength between titanium dioxide and the fiber body in the subsequently prepared fiber, and preventing titanium dioxide from falling off during the alkali etching process.

[0016] The draft multiple is 5.5~6.5;

[0017] The inorganic salt is one or more of potassium salt, sodium salt and calcium salt;

[0018] The principle of maintaining stable dispersion of the pulp of the present invention is as follows:

[0019] (1) By controlling the content of coated modified titanium dioxide in the spinning melt, the particle size of the coated modified titanium dioxide, and the drafting multiple, a large number of protrusions can be formed on the fiber surface, forming a rough surface different from the smooth surface of ordinary chemical fibers. A large number of capillary-like channels are formed between the protrusions of the fibers. Water molecules spread rapidly on the fiber surface and penetrate rapidly between the fibers with the help of capillary effect, which improves the wettability of water molecules between the fibers and makes the fibers quickly dispersed into a single fiber state;

[0020] (2) Alkaline etching treatment can remove the oligomers on the protruding part of the modified titanium dioxide coated on the fiber surface, exposing the titanium dioxide. The surface of the titanium dioxide is grafted with an amino-containing coupling agent. The amino-containing coupling agent combines with the metal ions in the inorganic salt to make the surface of the fiber carry a positive charge. After the fibers in the slurry are charged with the same charge, the fibers repel each other and separate, making it difficult for them to agglomerate and settle, and they can maintain a stable dispersion for a long time.

[0021] As the preferred technical solution:

[0022] In the above-mentioned method for preparing polyester fiber pulp, the steps for preparing the coated modified titanium dioxide are as follows:

[0023] (a) organically modifying titanium dioxide with a coupling agent to obtain coupling agent-modified titanium dioxide;

[0024] (b) adding the dibasic acid and diol into a reaction kettle, stirring and heating to 200-230°C, controlling the pressure of the reaction system to be 0.2-0.3MPa, adding a catalyst after reacting for 3-5h, controlling the temperature of the reaction system to gradually rise to 260-270°C, evacuating to a vacuum degree of less than 80Pa, reacting for 2-3h, cooling to 230°C, and obtaining an oligomer;

[0025] The dibasic acid is terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol and butanediol; the catalyst is ethylene glycol antimony or tetrabutyl titanate; the molar ratio of the dibasic acid to the diol is 1:0.9-0.95; the mass of the catalyst is 0.01-0.1% of the mass of the dibasic acid;

[0026] (c) adding coupling agent modified titanium dioxide to the reaction system of step (b), stirring at high speed to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and air flow crushing to obtain coated modified titanium dioxide;

[0027] The mass ratio of coupling agent modified titanium dioxide to oligomer is 5~8:1.

[0028] In the method for preparing polyester fiber pulp as described above, solid phase thickening is carried out under nitrogen or inert gas atmosphere, at a temperature of 190-210° C., and for a time of 24-48 hours.

[0029] In the method for preparing polyester fiber pulp as described above, the preheating temperature is 70-80° C. and the preheating can be carried out by water bath heating.

[0030] In the method for preparing polyester fiber pulp as described above, four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 100-120°C, the temperature of the second pair of drafting rollers is 130-150°C, the temperature of the third pair of drafting rollers is 180-200°C, and the temperature of the fourth pair of drafting rollers is 200-240°C; the spinning speed of the first pair of drafting rollers is 400-500 m / min, the spinning speed of the second pair of drafting rollers is 1200-1500 m / min, the spinning speed of the third pair of drafting rollers is 2400-2600 m / min, and the spinning speed of the fourth pair of drafting rollers is 2600-2800 m / min.

[0031] In the method for preparing polyester fiber pulp as described above, the heat setting temperature is 100° C. and the heat setting can be carried out by steam treatment.

[0032] In the preparation method of polyester fiber pulp as described above, the alkali etching process is as follows: placing the fiber in an alkali solution, heating it to 130°C at a heating rate of 2°C / min in an infrared dyeing machine, keeping it warm for 40 minutes, and then performing post-treatment (washing, drying, and drying at 105°C for 2 hours), wherein the ratio of fiber to alkali solution is 1g:50mL, the alkali solution is composed of NaOH, benzyl alcohol and water, the concentration of NaOH is 6g / L, and the concentration of benzyl alcohol is 3mL / L.

[0033] According to the method for preparing polyester fiber pulp as described above, after cutting, the fibers with a length of 5 to 10 mm in the short fibers account for 50 to 60 wt%, the fibers with a length of 11 to 18 mm account for 30 to 40 wt%, and the remaining part is fibers with a length of 19 to 24 mm. Since the pulp contains fibers of three length ranges, they play the roles of being soft and delicate, maintaining the stiffness of the paper, and enhancing the strength of the paper by entanglement, which is beneficial to the comprehensive mechanical properties of the paper finally produced.

[0034] In the method for preparing polyester fiber pulp as described above, the beating degree is 40-60°SR, the content of inorganic salt in the slurry is 0.5-1wt%, and the content of short fibers is 30-50wt%.

[0035] The present invention also provides polyester fiber pulp prepared by the method for preparing polyester fiber pulp as described in any one of the above items, wherein the sedimentation volume fraction Vs / V of the polyester fiber pulp is 90-95%, and the ζ potential is 8-12 mV, indicating that the pulp has good stability and dispersibility.

[0036] The present invention also provides an application of the polyester fiber pulp as described above, wherein the polyester fiber pulp is sent to a papermaking machine for papermaking, and then the wet paper sheets are squeezed by a squeezing roller to remove excess water, and then dried in a blast drying oven at 70°C for 2 hours to finally form paper; the paper has a thickness of 0.2±0.02mm and a gram weight of 200±20g / m 2 , tensile strength is 11~13N / mm 2 The water contact angle is 3-5°, indicating that the paper prepared from the pulp of the present invention has good mechanical strength and wettability. This may be because the surface of the titanium dioxide modified by the coupling agent of the fiber carries a large number of amino functional groups. When the paper is formed, a large number of hydrogen bonds are formed between the fibers with the help of the amino groups.

[0037] Beneficial effects:

[0038] (1) The fiber surface of the present invention is distributed with a large number of protrusions, which form a rough surface of the fiber. A large number of capillary-like channels are formed between the protrusions of the fibers. These capillary-like channels enhance the capillary action of the fiber surface, allowing water molecules to spread rapidly on the fiber surface. They are also beneficial for the rapid penetration of water molecules between fibers, thereby improving the wettability of water molecules between fibers and allowing the fibers to quickly disperse into a single fiber state.

[0039] (2) The alkaline etching treatment of the present invention can remove the oligomers of the protruding part of the coated modified titanium dioxide on the fiber surface, so that the titanium dioxide is exposed. The surface of the titanium dioxide is grafted with a coupling agent containing amino groups. These amino groups combine with the metal ions in the inorganic salt to make the surface of the fiber carry a positive charge. After the fibers in the slurry are charged with the same charge, the fibers repel each other and separate, and are not easy to agglomerate and settle, so they can maintain stable dispersion for a long time.

[0040] (3) The paper prepared from the pulp of the present invention has good mechanical strength and wettability.

[0041] (4) The present invention does not require the use of a dispersant, thereby saving costs, reducing environmental pollution and wastewater, and facilitating the subsequent recycling of waste paper. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:

[0044] Average degree of polymerization: tested by gel permeation chromatography (GPC).

[0045] Sedimentation volume fraction Vs / V: The sedimentation method is used for testing. The specific steps are as follows: 100 ml of pulp is put into a beaker, and the stirring speed is set to 200 rpm. After stirring for 10 minutes, the pulp is immediately transferred to a measuring cylinder, and the scale value corresponding to the highest liquid level of the fibers in the suspension in the measuring cylinder is recorded at this time, which is recorded as the initial volume V; the suspension is allowed to stand for 30 minutes, and the scale value corresponding to the highest liquid level of the fibers in the suspension at the end of the standing period is recorded, which is recorded as the volume after standing Vs; the sedimentation volume fraction Vs / V is calculated.

[0046] Zeta potential: Zeta potential analyzer was used for testing.

[0047] Tensile strength: The test was conducted using a paper tensile testing machine, with the tensile speed set at 300 mm / min.

[0048] Water contact angle: tested using a contact angle tester.

[0049] Example 1

[0050] A method for preparing paper, the specific steps are as follows:

[0051] (1) Preparation of raw materials;

[0052] Coupling agent: γ-aminopropyltriethoxysilane;

[0053] Titanium dioxide;

[0054] Dibasic acid: terephthalic acid;

[0055] Diol: ethylene glycol;

[0056] Catalyst: Antimony glycol;

[0057] Polyester: PET with an average degree of polymerization of 600;

[0058] water;

[0059] Inorganic salts: potassium chloride;

[0060] Alkali solution: composed of NaOH, benzyl alcohol and water, with the concentration of NaOH being 6 g / L and the concentration of benzyl alcohol being 3 mL / L;

[0061] (2) preparing a spinning melt;

[0062] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 80°C, titanium dioxide is organically modified with a coupling agent for 2.5 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 5% of the mass of the titanium dioxide;

[0063] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to be 0.2MPa, add the catalyst after 4h of reaction, control the temperature of the reaction system to gradually rise to 270°C, evacuate to 75Pa, react for 2.5h and cool to 230°C to obtain an oligomer with an average degree of polymerization of 40; wherein the molar ratio of the dibasic acid to the diol is 1:0.95; the mass of the catalyst is 0.1% of the mass of the dibasic acid;

[0064] (2.3) Adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide with a D50 particle size of 50nm; wherein the mass ratio of coupling agent modified titanium dioxide to oligomer is 5:1;

[0065] (2.4) First, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 65 wt%, and then the masterbatch is solid-phase thickened for 48 hours at a temperature of 190°C in an atmosphere of nitrogen or inert gas, and then the solid-phase thickened masterbatch is melt-blended with the polyester to obtain a spinning melt containing 20 wt% of the coated modified titanium dioxide;

[0066] (3) Preparation of staple fibers;

[0067] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing (using four pairs of drawing rollers) → heat setting → alkali etching treatment (placing the fiber in alkali solution at a mass volume ratio of 1g:50mL, heating to 130℃ at a heating rate of 2℃ / min, keeping the temperature for 40min, and then post-processing) → cutting;

[0068] Among them, the preheating temperature is 80°C, the temperature of the first pair of drafting rollers is 100°C, the temperature of the second pair of drafting rollers is 135°C, the temperature of the third pair of drafting rollers is 180°C, and the temperature of the fourth pair of drafting rollers is 200°C; the spinning speed of the first pair of drafting rollers is 400m / min, the spinning speed of the second pair of drafting rollers is 1250m / min, the spinning speed of the third pair of drafting rollers is 2500m / min, and the spinning speed of the fourth pair of drafting rollers is 2600m / min, and the heat setting temperature is 100°C;

[0069] After cutting, the proportion of fibers with a length of 5-10 mm in the staple fibers is 55wt%, the proportion of fibers with a length of 11-18 mm is 35wt%, and the remaining part is fibers with a length of 19-24 mm;

[0070] (4) Preparing polyester fiber pulp;

[0071] The short fibers, water and inorganic salt are mixed and then beaten to a beating degree of 55°SR to obtain polyester fiber pulp; wherein the content of the inorganic salt in the pulp is 0.7wt%, and the content of the short fibers is 40wt%;

[0072] The sedimentation volume fraction Vs / V of the prepared polyester fiber pulp was 93.8%, and the ζ potential was 9.7 mV;

[0073] (5) Preparation of paper;

[0074] After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to obtain paper.

[0075] The thickness of the final paper is 0.21mm and the weight is 212g / m 2 , tensile strength is 12.5N / mm, and water contact angle is 3.8°.

[0076] Comparative Example 1

[0077] A method for preparing paper is basically the same as that of Example 1, except that the inorganic salt is replaced by water of equal mass.

[0078] In step (4), the sedimentation volume fraction Vs / V of the polyester fiber pulp obtained is 46%, and the ζ potential is 3.9 mV; the tensile strength of the paper finally obtained is 5.4 N / mm, and the water contact angle is 4.8°.

[0079] By comparing Example 1 with Comparative Example 1, it can be seen that the stability and dispersibility of the polyester fiber pulp, and the mechanical strength and wettability of the paper prepared in Comparative Example 1 are significantly reduced. This is because in Comparative Example 1, the inorganic salt is replaced by an equal mass of water, so that the fiber surface cannot be positively charged by the combination of the amino-containing coupling agent and the metal ions in the inorganic salt, and the fibers lack the mutual repulsion caused by the same charges, and thus agglomeration and sedimentation are easily caused, resulting in a significant reduction in the stability and dispersibility of the polyester fiber pulp; at the same time, the reduction in the stability and dispersibility of the polyester fiber pulp will further affect the entanglement between the fibers in the process of preparing the paper, thereby resulting in a reduction in the mechanical strength and wettability of the paper.

[0080] Comparative Example 2

[0081] A method for preparing paper is basically the same as Example 1, except that the D50 particle size of the coated modified titanium dioxide in step (2.3) is 40 nm.

[0082] In step (4), the sedimentation volume fraction Vs / V of the polyester fiber pulp obtained is 73%, and the ζ potential is 6.2 mV; the tensile strength of the paper finally obtained is 9.6 N / mm, and the water contact angle is 7.9°.

[0083] By comparing Example 1 with Comparative Example 2, it can be seen that the stability and dispersibility of the polyester fiber pulp, the mechanical strength and wettability of the paper prepared in Comparative Example 2 are significantly reduced. This is because the D50 particle size of the coated modified titanium dioxide in Comparative Example 2 is too small, making it difficult to form a sufficient number of protrusion structures on the fiber surface, resulting in the inability to form sufficient and effective capillary-like channels between the fibers, which is not conducive to the rapid spreading of water molecules on the fiber surface and the rapid penetration between the fibers by means of capillary effect, thereby affecting the state of the fibers being quickly dispersed into single fibers, resulting in a significant reduction in the stability and dispersibility of the polyester fiber pulp; at the same time, the reduction in the stability and dispersibility of the polyester fiber pulp will further affect the entanglement between the fibers in the process of preparing the paper, thereby resulting in a reduction in the mechanical strength and wettability of the paper.

[0084] Example 2

[0085] A method for preparing paper, the specific steps are as follows:

[0086] (1) Preparation of raw materials;

[0087] Coupling agent: γ-aminopropyltriethoxysilane;

[0088] Titanium dioxide;

[0089] Dibasic acid: terephthalic acid;

[0090] Diol: ethylene glycol;

[0091] Catalyst: Antimony glycol;

[0092] Polyester: PET with an average degree of polymerization of 600;

[0093] water;

[0094] Inorganic salts: sodium chloride;

[0095] Alkali solution: composed of NaOH, benzyl alcohol and water, with the concentration of NaOH being 6 g / L and the concentration of benzyl alcohol being 3 mL / L;

[0096] (2) preparing a spinning melt;

[0097] (2.1) In a high-speed blender, at a speed of 2800 r / min and a temperature of 100° C., titanium dioxide is organically modified with a coupling agent for 2.8 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 3% of the mass of the titanium dioxide;

[0098] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to be 0.2MPa, add the catalyst after reacting for 3.5h, control the temperature of the reaction system to gradually rise to 265°C, evacuate to 78Pa, react for 2.5h and cool to 230°C to obtain an oligomer with an average degree of polymerization of 45; wherein the molar ratio of the dibasic acid to the diol is 1:0.92; the mass of the catalyst is 0.04% of the mass of the dibasic acid;

[0099] (2.3) Adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.7h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide with a D50 particle size of 200nm; wherein the mass ratio of coupling agent modified titanium dioxide to oligomer is 8:1;

[0100] (2.4) First, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 65 wt%, and then the masterbatch is solid-phase thickened for 30 hours in an atmosphere of nitrogen or inert gas at a temperature of 195°C. Then, the masterbatch after solid-phase thickening is melt-blended with the polyester to obtain a spinning melt containing 15 wt% of the coated modified titanium dioxide;

[0101] (3) Preparation of staple fibers;

[0102] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing (using four pairs of drawing rollers) → heat setting → alkali etching treatment (placing the fiber in alkali solution at a mass volume ratio of 1g:50mL, heating to 130℃ at a heating rate of 2℃ / min, keeping the temperature for 40min, and then post-processing) → cutting;

[0103] Among them, the preheating temperature is 75°C, the temperature of the first pair of drafting rollers is 100°C, the temperature of the second pair of drafting rollers is 130°C, the temperature of the third pair of drafting rollers is 180°C, and the temperature of the fourth pair of drafting rollers is 210°C; the spinning speed of the first pair of drafting rollers is 400m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2400m / min, and the spinning speed of the fourth pair of drafting rollers is 2600m / min, and the heat setting temperature is 100°C;

[0104] After cutting, the proportion of fibers with a length of 5-10 mm in the short fibers is 60wt%, the proportion of fibers with a length of 11-18 mm is 30wt%, and the remaining part is fibers with a length of 19-24 mm;

[0105] (4) Preparing polyester fiber pulp;

[0106] The short fibers, water and inorganic salt are mixed and then beaten to a beating degree of 40°SR to obtain polyester fiber pulp; wherein the content of the inorganic salt in the pulp is 0.5wt%, and the content of the short fibers is 30wt%;

[0107] The sedimentation volume fraction Vs / V of the prepared polyester fiber pulp was 95%, and the ζ potential was 8.5 mV;

[0108] (5) Preparation of paper;

[0109] After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to obtain paper.

[0110] The final paper thickness is 0.2mm and the weight is 204g / m 2 , tensile strength is 12.2N / mm, and water contact angle is 3.5°.

[0111] Comparative Example 3

[0112] A method for preparing paper is basically the same as that of Example 2, except that in step (2.4), the content of coated modified titanium dioxide in the spinning melt is 12 wt %.

[0113] In step (4), the sedimentation volume fraction Vs / V of the polyester fiber pulp obtained is 84%, and the ζ potential is 7.7 mV; the tensile strength of the paper finally obtained is 10.8 N / mm, and the water contact angle is 5.2°.

[0114] By comparing Example 2 with Comparative Example 3, it can be seen that the stability and dispersibility of the polyester fiber pulp prepared in Comparative Example 3, and the mechanical strength and wettability of the paper are significantly reduced. This is because the content of coated modified titanium dioxide in the spinning melt in Comparative Example 3 is too low, which reduces the number of protrusion structures formed on the fiber surface and makes the distribution less dense, making it difficult to form sufficient and effective capillary-like channels between the fibers, and the effect of water molecules rapidly spreading on the fiber surface and rapidly penetrating between the fibers by means of capillary effect becomes poor, which is not conducive to the rapid dispersion of the fibers into a single fiber state, thereby significantly reducing the stability and dispersibility of the polyester fiber pulp; at the same time, the reduced stability and dispersibility of the polyester fiber pulp will further affect the entanglement between the fibers in the process of preparing the paper, thereby reducing the mechanical strength and wettability of the paper.

[0115] Example 3

[0116] A method for preparing paper, the specific steps are as follows:

[0117] (1) Preparation of raw materials;

[0118] Coupling agent: γ-aminopropyltriethoxysilane;

[0119] Titanium dioxide;

[0120] Dibasic acid: terephthalic acid;

[0121] Diol: Propylene glycol;

[0122] Catalyst: Antimony glycol;

[0123] Polyester: PET with an average degree of polymerization of 720;

[0124] water;

[0125] Inorganic salts: calcium chloride;

[0126] Alkali solution: composed of NaOH, benzyl alcohol and water, with the concentration of NaOH being 6 g / L and the concentration of benzyl alcohol being 3 mL / L;

[0127] (2) preparing a spinning melt;

[0128] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 100° C., titanium dioxide is organically modified with a coupling agent for 2 h to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 3.5% of the mass of the titanium dioxide;

[0129] (2.2) Add the dibasic acid and diol into the reaction kettle, stir and heat to 210°C, control the pressure of the reaction system to be 0.23MPa, add the catalyst after reacting for 3h, control the temperature of the reaction system to gradually rise to 268°C, evacuate to 70Pa, react for 2h and cool to 230°C to obtain an oligomer with an average degree of polymerization of 60; wherein the molar ratio of the dibasic acid to the diol is 1:0.9; the mass of the catalyst is 0.01% of the mass of the dibasic acid;

[0130] (2.3) Adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and air flow crushing to obtain coated modified titanium dioxide with a D50 particle size of 500 nm; wherein the mass ratio of coupling agent modified titanium dioxide to oligomer is 7:1;

[0131] (2.4) First, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 55 wt%, and then the masterbatch is solid-phase thickened for 24 hours at a temperature of 200 °C in an atmosphere of nitrogen or inert gas, and then the masterbatch after solid-phase thickening is melt-blended with the polyester to obtain a spinning melt containing 18 wt% of the coated modified titanium dioxide;

[0132] (3) Preparation of staple fibers;

[0133] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing (using four pairs of drawing rollers) → heat setting → alkali etching treatment (placing the fiber in alkali solution at a mass volume ratio of 1g:50mL, heating to 130℃ at a heating rate of 2℃ / min, keeping the temperature for 40min, and then post-processing) → cutting;

[0134] Among them, the preheating temperature is 75°C, the temperature of the first pair of drafting rollers is 120°C, the temperature of the second pair of drafting rollers is 150°C, the temperature of the third pair of drafting rollers is 200°C, and the temperature of the fourth pair of drafting rollers is 240°C; the spinning speed of the first pair of drafting rollers is 430m / min, the spinning speed of the second pair of drafting rollers is 1300m / min, the spinning speed of the third pair of drafting rollers is 2500m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min, and the heat setting temperature is 100°C;

[0135] After cutting, the proportion of fibers with a length of 5-10 mm in the staple fibers is 50wt%, the proportion of fibers with a length of 11-18 mm is 40wt%, and the remaining part is fibers with a length of 19-24 mm;

[0136] (4) Preparing polyester fiber pulp;

[0137] The short fibers, water and inorganic salt are mixed and then beaten to a beating degree of 48°SR to obtain polyester fiber pulp; wherein the content of the inorganic salt in the pulp is 0.85wt%, and the content of the short fibers is 40wt%;

[0138] The sedimentation volume fraction Vs / V of the prepared polyester fiber pulp was 90.6% and the ζ potential was 10 mV;

[0139] (5) Preparation of paper;

[0140] After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to obtain paper.

[0141] The thickness of the final paper is 0.18mm and the weight is 193g / m 2 , tensile strength is 11.5N / mm, and water contact angle is 4.2°.

[0142] Example 4

[0143] A method for preparing paper, the specific steps are as follows:

[0144] (1) Preparation of raw materials;

[0145] Coupling agent: γ-aminopropyltrimethoxysilane;

[0146] Titanium dioxide;

[0147] Dibasic acid: terephthalic acid;

[0148] Diol: Butanediol;

[0149] Catalyst: tetrabutyl titanate;

[0150] Polyester: PET with an average degree of polymerization of 720;

[0151] water;

[0152] Inorganic salts: sodium chloride;

[0153] Alkali solution: composed of NaOH, benzyl alcohol and water, with the concentration of NaOH being 6 g / L and the concentration of benzyl alcohol being 3 mL / L;

[0154] (2) preparing a spinning melt;

[0155] (2.1) In a high-speed blender, at a speed of 2500 r / min and a temperature of 90°C, titanium dioxide is organically modified with a coupling agent for 3 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 4.5% of the mass of the titanium dioxide;

[0156] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 230°C, control the pressure of the reaction system to be 0.3MPa, add the catalyst after reacting for 5h, control the temperature of the reaction system to gradually rise to 270°C, evacuate to 65Pa, react for 3h and cool to 230°C to obtain an oligomer with an average degree of polymerization of 55; wherein the molar ratio of the dibasic acid to the diol is 1:0.92; the mass of the catalyst is 0.1% of the mass of the dibasic acid;

[0157] (2.3) Adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.8h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide with a D50 particle size of 700nm; wherein the mass ratio of coupling agent modified titanium dioxide to oligomer is 6:1;

[0158] (2.4) First, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 60 wt%, and then the masterbatch is solid-phase thickened for 30 hours at a temperature of 205°C in an atmosphere of nitrogen or inert gas, and then the solid-phase thickened masterbatch is melt-blended with the polyester to obtain a spinning melt containing 15 wt% of the coated modified titanium dioxide;

[0159] (3) Preparation of staple fibers;

[0160] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing (using four pairs of drawing rollers) → heat setting → alkali etching treatment (placing the fiber in alkali solution at a mass volume ratio of 1g:50mL, heating to 130℃ at a heating rate of 2℃ / min, keeping the temperature for 40min, and then post-processing) → cutting;

[0161] Among them, the preheating temperature is 78°C, the temperature of the first pair of drafting rollers is 105°C, the temperature of the second pair of drafting rollers is 135°C, the temperature of the third pair of drafting rollers is 190°C, and the temperature of the fourth pair of drafting rollers is 220°C; the spinning speed of the first pair of drafting rollers is 450m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2400m / min, and the spinning speed of the fourth pair of drafting rollers is 2650m / min, and the heat setting temperature is 100°C;

[0162] After cutting, the proportion of fibers with a length of 5-10 mm in the staple fibers was 55wt%, the proportion of fibers with a length of 11-18 mm was 38wt%, and the remaining part was fibers with a length of 19-24 mm.

[0163] (4) Preparing polyester fiber pulp;

[0164] The short fibers, water and inorganic salt are mixed and then beaten to a beating degree of 60°SR to obtain polyester fiber pulp; wherein the content of the inorganic salt in the pulp is 1wt%, and the content of the short fibers is 50wt%;

[0165] The sedimentation volume fraction Vs / V of the prepared polyester fiber pulp was 91%, and the ζ potential was 12 mV;

[0166] (5) Preparation of paper;

[0167] After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to obtain paper.

[0168] The final paper thickness is 0.19mm and the weight is 198g / m 2 , tensile strength is 12N / mm, and water contact angle is 4.5°.

[0169] Example 5

[0170] A method for preparing paper, the specific steps are as follows:

[0171] (1) Preparation of raw materials;

[0172] Coupling agent: γ-aminopropyltrimethoxysilane;

[0173] Titanium dioxide;

[0174] Dibasic acid: terephthalic acid;

[0175] Diol: Butanediol;

[0176] Catalyst: tetrabutyl titanate;

[0177] Polyester: PET with an average degree of polymerization of 720;

[0178] water;

[0179] Inorganic salts: sodium chloride;

[0180] Alkali solution: composed of NaOH, benzyl alcohol and water, with the concentration of NaOH being 6 g / L and the concentration of benzyl alcohol being 3 mL / L;

[0181] (2) preparing a spinning melt;

[0182] (2.1) In a high-speed blender, at a speed of 2800 r / min and a temperature of 90°C, titanium dioxide is organically modified with a coupling agent for 2.5 hours to obtain coupling agent-modified titanium dioxide; wherein the mass of the coupling agent is 4% of the mass of the titanium dioxide;

[0183] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to be 0.28MPa, add the catalyst after reacting for 4h, control the temperature of the reaction system to gradually rise to 260°C, evacuate to 75Pa, react for 2.8h and cool to 230°C to obtain an oligomer with an average degree of polymerization of 60; wherein the molar ratio of the dibasic acid to the diol is 1:0.95; the mass of the catalyst is 0.08% of the mass of the dibasic acid;

[0184] (2.3) Adding coupling agent modified titanium dioxide to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified titanium dioxide with a D50 particle size of 900nm; wherein the mass ratio of coupling agent modified titanium dioxide to oligomer is 8:1;

[0185] (2.4) First, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch with a concentration of 50 wt%, and then the masterbatch is solid-phase thickened for 24 hours in an atmosphere of nitrogen or inert gas at a temperature of 210°C, and then the solid-phase thickened masterbatch is melt-blended with the polyester to obtain a spinning melt containing 20 wt% of the coated modified titanium dioxide;

[0186] (3) Preparation of staple fibers;

[0187] The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing (using four pairs of drawing rollers) → heat setting → alkali etching treatment (placing the fiber in alkali solution at a mass volume ratio of 1g:50mL, heating to 130℃ at a heating rate of 2℃ / min, keeping the temperature for 40min, and then post-processing) → cutting;

[0188] Among them, the preheating temperature is 70°C, the temperature of the first pair of drafting rollers is 110°C, the temperature of the second pair of drafting rollers is 145°C, the temperature of the third pair of drafting rollers is 195°C, and the temperature of the fourth pair of drafting rollers is 235°C; the spinning speed of the first pair of drafting rollers is 500m / min, the spinning speed of the second pair of drafting rollers is 1500m / min, the spinning speed of the third pair of drafting rollers is 2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min, and the heat setting temperature is 100°C;

[0189] After cutting, the proportion of fibers with a length of 5-10 mm in the staple fibers is 60wt%, the proportion of fibers with a length of 11-18 mm is 32wt%, and the remaining part is fibers with a length of 19-24 mm;

[0190] (4) Preparing polyester fiber pulp;

[0191] The short fibers, water and inorganic salt are mixed and then beaten to a beating degree of 50°SR to obtain polyester fiber pulp; wherein the content of the inorganic salt in the pulp is 1wt%, and the content of the short fibers is 45wt%;

[0192] The sedimentation volume fraction Vs / V of the prepared polyester fiber pulp was 92.5%, and the ζ potential was 11.3 mV;

[0193] (5) Preparation of paper;

[0194] After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to obtain paper.

[0195] The thickness of the final paper is 0.22mm and the weight is 216g / m 2 , tensile strength is 12.7N / mm, and water contact angle is 4.3°.

[0196] Comparative Example 4

[0197] A method for preparing paper is basically the same as Example 5, except that the spinning speed of the fourth pair of drafting rollers in step (3) is 2600 m / min.

[0198] In step (4), the sedimentation volume fraction Vs / V of the polyester fiber pulp obtained is 82%, and the ζ potential is 7.4 mV; the tensile strength of the paper finally obtained is 9.5 N / mm, and the water contact angle is 6.5°.

[0199] By comparing Example 5 with Comparative Example 4, it can be seen that the stability and dispersibility of the polyester fiber pulp prepared in Comparative Example 4, and the mechanical strength and wettability of the paper are significantly reduced. This is because the drafting in Comparative Example 4 is insufficient, so that the fibers cannot be fully refined and the ideal fiber surface structure cannot be shaped during the drafting process, resulting in a decrease in the number of protrusions formed on the fiber surface and insufficient distribution, and it is difficult to form sufficient and effective capillary-like channels between fibers. The rapid spreading of water molecules on the fiber surface and the rapid penetration between fibers by means of capillary effect will be hindered, which is not conducive to the rapid dispersion of the fibers into a single fiber state, thereby causing a significant decrease in the stability and dispersibility of the polyester fiber pulp; at the same time, the decrease in the stability and dispersibility of the polyester fiber pulp will further affect the entanglement between fibers in the process of preparing paper, thereby causing a decrease in the mechanical strength and wettability of the paper.

Claims

1. A method for preparing polyester fiber pulp, characterized in that: The short fibers, water and inorganic salts are mixed and then beaten to obtain polyester fiber pulp; The preparation process of staple fibers is as follows: spinning melt is extruded from the spinneret → oiling → bundling → extrusion deformation → preheating → drawing → heat setting → alkali etching → cutting; The spinning melt contains 15-20wt% of coated modified titanium dioxide; the D50 particle size of the coated modified titanium dioxide is 50-900nm; the coated modified titanium dioxide includes titanium dioxide and oligomers coated on the surface thereof by covalent bonds, and the oligomers are different from the matrix of the spinning melt only in average polymerization degree, and the average polymerization degree of the oligomers is 40-60; The preparation method of the coated modified titanium dioxide is as follows: firstly, an amino-containing coupling agent is used to organically modify titanium dioxide to obtain coupling agent-modified titanium dioxide, and at the same time, an oligomer is prepared, and then the oligomer and the coupling agent-modified titanium dioxide are mixed and reacted; The preparation process of the spinning melt is as follows: firstly, the polyester and the coated modified titanium dioxide are melt-blended to obtain a masterbatch, then the masterbatch is solid-phase thickened, and then the masterbatch after solid-phase thickening is melt-blended with the polyester to obtain a spinning melt; The draft multiple is 5.5~6.5; The inorganic salt is one or more of potassium salt, sodium salt and calcium salt.

2. The method for preparing polyester fiber pulp according to claim 1, characterized in that: The preparation steps of coated modified titanium dioxide are as follows: (a) organically modifying titanium dioxide with a coupling agent to obtain coupling agent-modified titanium dioxide; (b) adding the dibasic acid and diol into a reaction kettle, stirring and heating to 200-230°C, controlling the pressure of the reaction system to be 0.2-0.3MPa, adding a catalyst after reacting for 3-5h, controlling the temperature of the reaction system to gradually rise to 260-270°C, evacuating to a vacuum degree of less than 80Pa, reacting for 2-3h, cooling to 230°C, and obtaining an oligomer; (c) Add the coupling agent modified titanium dioxide to the reaction system of step (b), stir to fully mix, keep the temperature to react for 0.5 to 1 hour, continue to evacuate, discharge, cool, pre-crush, and air flow crush to obtain coated modified titanium dioxide.

3. The method for preparing polyester fiber pulp according to claim 1, characterized in that: The solid phase adhesion is carried out in a nitrogen or inert gas atmosphere at a temperature of 190-210°C for 24-48 hours.

4. The method for preparing polyester fiber pulp according to claim 1, characterized in that: The preheating temperature is 70~80℃.

5. The method for preparing polyester fiber pulp according to claim 1, characterized in that: Four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 100~120℃, the temperature of the second pair of drafting rollers is 130~150℃, the temperature of the third pair of drafting rollers is 180~200℃, and the temperature of the fourth pair of drafting rollers is 200~240℃; the spinning speed of the first pair of drafting rollers is 400~500m / min, the spinning speed of the second pair of drafting rollers is 1200~1500m / min, the spinning speed of the third pair of drafting rollers is 2400~2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2600~2800m / min.

6. The method for preparing polyester fiber pulp according to claim 1, characterized in that: The process of alkali etching treatment is: placing the fiber in alkali solution, heating it to 130°C at a heating rate of 2°C / min, keeping it warm for 40 minutes, and then performing post-treatment, wherein the ratio of fiber to alkali solution is 1g:50mL, the alkali solution is composed of NaOH, benzyl alcohol and water, the concentration of NaOH is 6g / L, and the concentration of benzyl alcohol is 3mL / L.

7. The method for preparing polyester fiber pulp according to claim 1, characterized in that: After cutting, the fibers with a length of 5 to 10 mm account for 50 to 60 wt% of the staple fibers, the fibers with a length of 11 to 18 mm account for 30 to 40 wt%, and the remaining fibers are fibers with a length of 19 to 24 mm.

8. The method for preparing polyester fiber pulp according to claim 1, characterized in that: The beating degree is 40~60°SR, the content of inorganic salt in the slurry is 0.5~1wt%, and the content of short fibers is 30~50wt%.

9. The polyester fiber pulp prepared by the method for preparing polyester fiber pulp according to any one of claims 1 to 8, characterized in that: The sedimentation volume fraction Vs / V of polyester fiber pulp is 90~95%, and the ζ potential is 8~12mV.

10. The use of polyester fiber pulp according to claim 9, characterized in that: After the polyester fiber pulp is sent to the papermaking machine for papermaking, it is squeezed to remove excess water and dried to finally make paper; the thickness of the paper is 0.2±0.02mm and the gram weight is 200±20g / m 2 , tensile strength is 11~13N / mm 2 , the water contact angle is 3~5°.

Citation Information

Patent Citations

  • Preparing method of high-strength wrapping chemical fiber paper

    CN107419573A

  • Cellulose acetate fiber / plant fiber composite paper and preparation method and application thereof

    CN117604804A

  • Quick-dry heat sublimation transfer paper

    CN220700751U

  • Polymer masterbatch for preparing high moisture absorption and high moisture exclusion polyester textile and synthetic method thereof

    CN101104729A

  • Low VOC (Volatile Organic Compound) regenerated polyester fiber and preparation method thereof

    CN108396404A